If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(f + 5) + -8 = 2f Reorder the terms: 6(5 + f) + -8 = 2f (5 * 6 + f * 6) + -8 = 2f (30 + 6f) + -8 = 2f Reorder the terms: 30 + -8 + 6f = 2f Combine like terms: 30 + -8 = 22 22 + 6f = 2f Solving 22 + 6f = 2f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2f' to each side of the equation. 22 + 6f + -2f = 2f + -2f Combine like terms: 6f + -2f = 4f 22 + 4f = 2f + -2f Combine like terms: 2f + -2f = 0 22 + 4f = 0 Add '-22' to each side of the equation. 22 + -22 + 4f = 0 + -22 Combine like terms: 22 + -22 = 0 0 + 4f = 0 + -22 4f = 0 + -22 Combine like terms: 0 + -22 = -22 4f = -22 Divide each side by '4'. f = -5.5 Simplifying f = -5.5
| 19u-18u=5 | | 4y-30=y+8+2y-3 | | 200(1)-15=y | | .9x-4.9=.5 | | 5*3v-8=-10 | | -0.25(q-1)+0.5=0.75 | | 200m-75m+57900=61500-175m | | 9x+5(x-2)=2(x-3) | | X^2-2px+9=0 | | [(x)(x)]-7x=44 | | 36-9x=19+8x | | 6p-7=-5p+12 | | 200(1)+15=y | | 4x-2x+15-10-6=19 | | 5y-3=2y-15 | | 200(0)+15=y | | 6-9x=6x-10x+1 | | C=3(a+2b) | | -14=8+h | | 3x+2x-18+13=35 | | 9(3m+4)-7m=-4 | | 200(0)-15=y | | 15q-3[4q-6]=3q+9-9q | | 5x+4=26+46 | | 0.3(3x+0.5)= | | -2(5x+2)=-3x+7 | | 12=6ax-4xb | | -25-(-15)= | | 3+y4=-y8 | | 10(12)=5(18) | | 47-6x=19+8x | | 7Z-3y=2 |